The “Open + Liquid + Flexible” Public Hospital Management Model Made in Vietnam: Lessons Learnt for Adapting to the COVID-19 Pandemic in Vietnam - Minh, Nguyen Dang; Thanh, Nguyen Tien; Dung, Nguyen Thuy; Thuy, Nguyen Thi Thanh (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 2 No 3, 2022)
The COVID-19 pandemic started in the early 2020 has significantly hit every human-life aspect in  all over the world, especially the medical industry. To ensure both regular and irregular healthcare work (i.e., prevention, treatment for COVID-19 patients), hospitals are required to change their thinking and management model. This research creates an “open + liquid + flexible” public hospital management model made in Vietnam, based on the theory of Made in Vietnam lean management and practical lessons learnt for adaptations to the COVID-19 pandemic in the past two years.